2000
DOI: 10.1007/bf02490486
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical optimization of analyte collection in analytical supercritical fluid extraction

Abstract: SummaryOptimizing the extracted analyte collection step in analytical supercritical fluid extraction (SFE) is of key importance in achieving high analyte recoveries and extraction efficiencies. Whereas the extraction step in SFE has been well characterized both theoretically and experimentally; the analyte collection step after SFE has few theoretical guidelines, aside from a few empirical studies which have appeared in the literature. In this study, we have applied several theoretical approaches using experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2002
2002
2005
2005

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…As the solvent ratio increases, the superficial velocity of SC-CO 2 increases, and the external resistance to mass transfer in a thin stationary film near the boldo particles decreases; the end result being an increase in mass transfer rate. However, as this velocity increases beyond an optimal, system-dependent value, ''operational solubility'' values may be influenced by axial dispersion phenomena (Rodrigues et al, 2002) and/or entrainment of solute droplets by the gaseous CO 2 leaving the glass vials (King & Zhang, 2000;Turner, Eskilsson, & Bjorklund, 2002;Waldmann & Eggers, 1991). In our experiments, the total extract yield was 36% higher using 2.12 than 1.51 g/g substrate/min of CO 2 at 50°C and 90 bar.…”
Section: Characterization Of Boldo Leaf Samplesmentioning
confidence: 68%
“…As the solvent ratio increases, the superficial velocity of SC-CO 2 increases, and the external resistance to mass transfer in a thin stationary film near the boldo particles decreases; the end result being an increase in mass transfer rate. However, as this velocity increases beyond an optimal, system-dependent value, ''operational solubility'' values may be influenced by axial dispersion phenomena (Rodrigues et al, 2002) and/or entrainment of solute droplets by the gaseous CO 2 leaving the glass vials (King & Zhang, 2000;Turner, Eskilsson, & Bjorklund, 2002;Waldmann & Eggers, 1991). In our experiments, the total extract yield was 36% higher using 2.12 than 1.51 g/g substrate/min of CO 2 at 50°C and 90 bar.…”
Section: Characterization Of Boldo Leaf Samplesmentioning
confidence: 68%
“…For the collection of lipid extracts, it would appear that the open vial or sorbent-filled collection vial are most frequently used; the latter frequently employing some type of sub-ambient cooling to retain volatile species. King and Zhang (2000) have modelled solute trapping in a open vessel in terms of the retention efficiency of the analyte being collected and shown that trapping efficiency is related to the relative vapour pressures of the solute (analyte) and the solvent (supercritical fluid). Since CO2 upon decompression has a large fugacity, it is not unusal for the ratio of solvent/solute vapour pressures to exceed 10 3 .…”
mentioning
confidence: 99%